Клепіков Вячеслав Федорович (до 75-річчя від дня народження) - Azarenkov, M.O.; Babich, A.V.; Bazaleev, M.I.; Bryukhovetsky, V.V.; Bilous, V.A.; Bulavin, L.A.; Garkusha, I.Ye.; Girka, I.O.; Denisov, V.Y.; Zabulonov, Yu.L.; Karnauhov, I.M.; Kasatkin, Yu.O.; et al. (Publishing house "Academperiodika", 2024)
07.13.2024 75 years have passed since the birthday of Vyacheslav Fedorovych Klepikov, a well-known theoretical physicist, Doctor of physical and mathematical sciences, Professor, Correspondent member of the National Academy of Sciences of Ukraine.